Molecular characterization of a 31 kDa protein from Trichinella spiralis and its induced immune protection in BALB/c mice - Ren, Hua Nan (Parasit Vectors, 2018)
BACKGROUND: Trichinella spiralis is an important foodborne zoonotic parasite and it is necessary to develop a vaccine in order to interrupt transmission from animals to humans. A 31 kDa protein from T. spiralis (Ts31) is an antigen targeted by protective antibodies, and Ts31 contains a domain of trypsin-like serine protease that might have the function of serine protease. The purpose of this study was to investigate the molecular characteristics of Ts31 and its induced immune protection. METHODS: Expression and localization of Ts31 in various T. spiralis phases were investigated using qPCR and immunofluorescent test (IFT). The specific binding between Ts31 and intestinal epithelium cells (IECs) was analyzed by Far-Western blotting, ELISA and IFT, and the cellular localization of binding sites was examined on confocal microscopy. The mice were subcutaneously vaccinated with recombinant Ts31 protein (rTs31), serum specific IgG was determined by ELISA, and immune protection induced by immunization with rTs31 was evaluated. Inhibition of anti-rTs31 IgG on IL1 invasion of IECs and ADCC-mediated killing of newborn larvae (NBL) was also determined. RESULTS: Ts31 was expressed at different life-cycle stages and located principally at the stichosome and cuticle of this parasite. rTs31 was capable to specially bond to IECs, and binding site was located in the cytoplasm of IECs. Immunization of mice with rTs31 elicited a significant humoral response and protection, as demonstrated by a 56.93% reduction of adult worms at 6 days post-infection (dpi) and a 53.50% reduction of muscle larvae at 42 dpi after larval challenge. Anti-rTs31 antibodies impeded T. spiralis penetration of enterocytes in a dose-dependent pattern, and participated in the destruction of NBL by an ADCC-mediated manner. CONCLUSIONS: Ts31 facilitated the T. spiralis penetration of intestinal epithelium, which could make it a vaccine candidate target molecule against Trichinella infection.